How important is regional vs. global scope? An examination of U.S. multinationals - Jeong, Yujin; Siegel, Jordan I. (Journal of International Business Studies, 2020)
Beginning with Rugman and Verbeke (J Int Bus Stud 35(1):3–18, 2004), several international business (IB) scholars have proposed that most large multinationals are not global but regional. This argument has recently been challenged for both its conceptualization and its implementation. We aim to contribute to this debate by revisiting the definitions of regional and global, by leveraging data from the U.S. Bureau of Economic Analysis that is new to this literature, and by analyzing multinationals’ scope in terms of both sales and production. We find that U.S. multinationals are significantly more global than has previously been acknowledged in the IB literature.